Empowering Religious Counselors as Agents of Religious Moderation in the Indonesian Ministry of Religious Affairs - Hesti Kusumaningrum; Rubiyanah Rubiyanah; Indah Fadhilla (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2023)
AbstractThis study aims to analyze how a training model strengthens the competence of religious counselors in spreading the value of religious moderation. This research uses a qualitative approach of case study type by collecting data through in-depth interviews, observations, and literature studies. The research participants consisted of Religious Counselors working in various regions in Indonesia who participated in the education and training program for religious moderation activists conducted by the Indonesian Ministry of Religious Affairs training center. The results showed that Religious Counselors need to increase their understanding of the principles of religious moderation, practical communication skills, and conflict-handling strategies. In addition, the training model can strengthen the competencies of religious counselors in disseminating the value of religious moderation and conducting their duties as religious counselors. This training model uses an andragogy learning approach with group discussions, case studies, simulations, and team-based training methods. The training materials such as interfaith dialogue, the concept of religious moderation, religious diversity, religious tolerance, and conflict management can strengthen the understanding of Religious Counselors about pluralism and religious moderation, communication skills, and building interfaith cooperation. After attending this training, the counselors became more confident in carrying out their duties and more prepared to deal with religion-driven social conflicts in the community. Furthermore, they can develop digital media learning on religious moderation through social media.AbstrakMakalah ini bertujuan untuk menganalisis bagaimana model pelatihan untuk memperkuat kompetensi Penyuluh Agama dalam menyebarkan nilai moderasi agama. Penelitian ini menggunakan pendekatan kualitatif tipe studi kasus dengan mengumpulkan data melalui wawancara mendalam, observasi, dan studi literatur. Partisipan penelitian terdiri dari Penyuluh Agama yang bekerja di berbagai wilayah di Indonesia yang mengikuti program pendidikan dan pelatihan untuk aktivis moderasi agama yang diselenggarakan oleh pusat pelatihan Kementerian Agama Republik Indonesia. Hasil penelitian menunjukkan bahwa Penyuluh Agama perlu meningkatkan pemahaman mereka tentang prinsip-prinsip moderasi agama, keterampilan komunikasi efektif, dan strategi penanganan konflik. Selain itu, model pelatihan dapat memperkuat kompetensi Penyuluh Agama dalam menyebarkan nilai moderasi agama dalam menjalankan tugas mereka sebagai Penyuluh Agama. Model pelatihan ini menggunakan pendekatan pembelajaran andragogi dengan metode diskusi kelompok, studi kasus, simulasi, dan pelatihan berbasis tim. Materi pelatihan seperti dialog lintas agama, konsep moderasi agama, keragaman agama, toleransi beragama, dan manajemen konflik mampu memperkuat pemahaman Penyuluh Agama tentang pluralisme dan moderasi agama, keterampilan komunikasi, dan membangun kerjasama lintas agama. Setelah mengikuti pelatihan ini, Penyuluh menjadi lebih percaya diri dalam menjalankan tugas mereka, lebih siap dalam menghadapi konflik sosial keagamaan di masyarakat. Selain itu, mereka dapat mengembangkan pembelajaran media digital dengan tema moderasi agama melalui media sosial.How to Cite: Kusumaningrum, H., Rubiyanah., Fadhilla, I. (2023). Empowering Religious Counselors as Agents of Religious Moderation in the Indonesian Ministry of Religious Affairs. TARBIYA: Journal of Education in Muslim Society, 10(2), 219-236. doi:10.15408/tjems.v10i2.37771.